Developing a manualised task-sharing counselling intervention for perinatal common mental disorders in the South African context - Boisits, Sonet (Department of Psychology, 2022)
Background: Symptoms of depression and anxiety are highly prevalent amongst perinatal women in low-resource settings of South Africa, but there is no access to standardised counselling support for these conditions in public health facilities. The aim of this study was to report on the development of a maternal mental health counselling intervention for routine treatment of mild to moderate symptoms of depression and anxiety for primary healthcare in South Africa, as part of the Health Systems Strengthening in sub-Saharan Africa (ASSET) study. Methods: A four-phase study process informed the counselling intervention and training manual designed to train lay health workers. We first conducted a review of manuals from seven counselling interventions for depression and anxiety in low- and middle-income countries and two local health system training programmes to gather information on common counselling components used across maternal mental health and other evidence-based task-sharing interventions. Thereafter, semi-structured interviews were conducted with 20 health workers and 37 pregnant women from four Midwife Obstetric Units in Cape Town to explore mental health views and needs. In the third stage, multi-sector stakeholder engagements further informed the choice of intervention design and service provider. In the final phase, a four-day pre implementation pilot training with community-based health workers refined the counselling content and training material. Results: The manual review identified problem-solving, psychoeducation, basic counselling skills and behavioural activation as common counselling components across interventions. The interviews found that participants mostly identified symptoms of depression and anxiety in behavioural terms and lay health workers and pregnant women demonstrated their understanding through a range of contextual terms. Perceived causes of symptoms related to interpersonal conflict and challenging social circumstances. Stakeholder engagements identified a three session counselling model as most feasible for delivery as part of existing health care practices and community health workers in ward-based outreach teams as the best placed delivery agents. Pilot training of a three-session intervention with community-based health workers resulted in minor adaptations of the counselling assessment method. Conclusion: The study demonstrates how common therapeutic elements can be adapted to a local context and developed into an evidence-based manualised therapeutic programme while remaining sensitive to a health system's needs. While a problem-solving counselling approach, delivered in a structured format, was best suited for training lay health workers, input from health workers and perinatal mothers informed the manualised counselling content. The latter was a critical supplement to align the programme with contextual needs. Stakeholder engagements helped to align the intervention design to health system requirements and guidelines. Structured training practices and ongoing supervision of mental health workers are vital to develop counselling skills over time and to enhance personal support.